UPAYA PENGUATAN BRAND TRUST LIPSTIK WARDAH DI PLATFORM TIKTOK LIVE PADA GENERASI Z - Agista Nurul Defani; Diana Aqmala; Ariati Anomsari; Awanis Linati Haziroh (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
The purpose of this study is to analyze the influence of Customer Experience, Live Streaming, and Influencer Credibility on Brand Trust of Generation Z Wardah lipstick users through TikTok Live. This study uses a quantitative method, with data obtained from 170 Generation Z respondents in Semarang who have watched and interacted directly with the Wardah brand through TikTok live. Data analysis uses the PLS-SEM technique processed using SmartPLS 4 software. The results show that the three independent variables, namely Customer Experience, Live Streaming, and Influencer Credibility, have a positive and significant effect on Brand Trust. This shows that a pleasant Customer Experience, authentic and interactive interactions through live broadcasts, and the credibility of influencers who have similar expertise and values ​​to the audience, can increase consumer trust in the Wardah brand.